THE INFORMATIONAL TECHNIQUE AS A TOOL TO REDUCE PRIVACY ON THE WEB: ANALYSIS OF THE WIKILEAKS CASE - Marchetto, Patrícia Borba; Barrientos-Parra, Jorge David; Rodrigues, Gustavo Alarcon [UNESP] (Conselho Nacional de Pesquisa e Pos-Graduacao em Direito - CONPEDI, 2019)
The present work aims to analyze impacts caused by computer and information technologies, on human privacy, especially the internet and its accessory tools, directing the approach to State and large digital corporations’ behavior, these exposed by Wikileaks website. Therefore, it starts from an analysis of computational technique, its speed of expansion and its founding bases, aiming to understand the dynamics of power that are generated through the internet and their differences when compared to the power exercised in the “domain of atoms”. Through this, is sought to address the exposing form of power as privacy violations, connected to structuring means of control and surveillance. The work in question has as a methodological paradigm, at first, the deductive method, starting from general theoretical conceptions to understand the dynamics of forces on the internet. During the approach of the practical situation, the inductive method is used, demonstrating through the paradigmatic case how these forces operate under the cover of legality, proposing concepts that converge with the syntheses obtained deductively. It is important to note that there is the adoption of a bibliographic review of works, articles and news related to the theme as support for the chosen methodology.
A TÉCNICA INFORMACIONAL COMO FERRAMENTA DE REDUÇÃO DA PRIVACIDADE NA REDE: ANÁLISE DO CASO WIKILEAKS
Keywords: internet; privacy; surveillance; Wikileaks